Significant Antifungal Activity of Streptomyce Plicatus NM3 Against Clinically Relevant Candida Species Collected from Jazan Hospital - Alzahrani , Nourah S.; Amashah, Reda H.; Kameli , Nader M.; Aly, Magda M. (Journal of Contemporary Medical Sciences, 2025)
Objective: The purpose of this work was the biocontrol of Candida species from Jazan hospitals using non polyenic antifungal agent from actinomycetes. Methods: Different isolates of Candida were collected, identified by Vitek 2, their characterized growth was recorded on chromoagar medium and their identification was confirmed using molecular method. Some isolated actinomycetes were tested for their biocontrol activity of Candida isolates. Results: Twenty-four isolates of Candida species obtained from Jazan hospital were identified and most of them were belong to Candida albican, Candida auris, Candida parapsilosis, Candida tropicalis, Candida glabrata, and Candida ciferrii. Out of 39 actinomycete isolates, and using agar well diffusion method, the isolate NM3 which was morphologically, physiologically and molecually identified as Streptomyce plicatus NM3, inhibited many Candida isolates, specially C. parapsilosis, C. auris and C. tropicalis with inhibition zone diameter ranged from 19-21 mm. Excellent antifungal activities were recorded for the ethyl acetate extract and the presence of ergesterol in the cultivation medium decreased the antifungal activity. The UV spectra of the isolate NM3 extract showed non-polyenic antifungal structure. Conclusion: Streptomyce plicatus NM3 showed excellent activity against resistant Candida isolates and produce secondary products with non polyenic antifungal structure, thus it can be used for further studies.